An Approach to Developing Multi-Tenancy SaaS Using Metaprogramming - Rodrigues, Josino; Leite, Andreza; Damasceno, Júlio César; Garcia, Vinicius Cardoso; Meira, Silvio Romero Lemos; Silveira, Paulo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
In last years have seen an increase in SaaS (Software as a Service) use. The development of multi-tenancy web application (one of the main ways to provide SaaS) increased considerably after the start of call “Web 2.0 Age”. This work presents an approach for implementation of a multitenancy SaaS application, and an architecture based on plugins and metaprogramming to achieve a high level software reuse. This approach is presented through an experience report described throughout the paper.